Data Science in Marketing: How Analytics are Reshaping Consumer Insights - Kusuma, Jaya (Advances: Jurnal Ekonomi & Bisnis, 2024)
Purpose: The purpose of this study is to explore the transformative impact of data science on marketing strategies and consumer insights. Research Design and Methodology: Employing a qualitative research design, the study utilizes in-depth case studies and interviews with industry experts to uncover how data-driven approaches enhance traditional marketing practices. Findings and Discussion: The findings reveal that data science significantly improves customer segmentation, dynamic pricing, customer relationship management (CRM), and personalized marketing. By leveraging behavioral data, companies like Amazon achieve more granular and dynamic segmentation, leading to higher engagement and conversion rates. Dynamic pricing, as implemented by companies like Uber, optimizes revenue and enhances customer satisfaction through real-time adjustments based on demand and competition. The study also highlights the importance of predictive analytics in CRM, allowing businesses to identify at-risk customers and implement targeted retention strategies. Furthermore, ethical considerations such as data privacy and algorithmic bias are critical for maintaining consumer trust. Implications: The research underscores the need for integrating data science with traditional marketing frameworks and adapting models to diverse cultural contexts. The implications for practice include adopting data-driven segmentation, dynamic pricing, and CRM strategies while ensuring ethical data practices. This study contributes to the broader discourse on data-driven marketing, offering valuable insights for both academic research and practical applications, ultimately advocating for responsible and effective use of data science in marketing.